Towards the development of a feasible EU action plan against deforestation - Insights from the Indonesian palm oil sector - Jelsma I.; Jezeer, R.; Dam, J. van; Purwanto, E. (2020)
This brief focuses on the Indonesian oil palm sector and highlights key characteristics that must be considered when developing the EU legislative framework. This brief focuses on environmental impacts of proposed measures and other social issues. It describes the oil palm sector, initiatives that are shaping sustainability, and lessons learned, based on literature and experiences from Tropenbos Indonesia’s ongoing work in West Kalimantan, leading to key considerations that EU policymakers should take on board when developing their ambitious plans for more sustainable agrocommodity supply chains.